AN INNOVATIVE PARADIGM FOR STUDENTS LEARNING ENGLISH IN THE ERA OF ARTIFICIAL INTELLIGENCE - Kadyrakunova Karla; Aibolat S. Nabidullin (Modern Scientific Technology, 2025)
This article is devoted to the study of an innovative paradigm for learning English by students in the context of the rapid development of artificial intelligence (AI) technologies. It examines the psychological, cognitive, motivational, inclusive, and ethical aspects of applying AI in education. Particular attention is paid to how AI transforms students’ learning activities, increases the level of personalization, contributes to the development of communication skills, and forms a new model of interaction between students, AI, and teachers. The expanded ACCA-AI-LA approach is presented as an innovative methodology for teaching English in a digital educational environment